Exosomes: a new horizon in lung cancer. Issue 6 (June 2017) - Vanni, Irene; Alama, Angela; Grossi, Francesco; Dal Bello, Maria Giovanna; Coco, Simona
Highlights: Exosomes play a key part in tumorigenesis and progression of cancer. Exosomes can be isolated from cell culture media and almost all body fluids. Exosomes are cargos of DNA, mRNA, miRNAs and proteins. Exosomes are candidates as diagnostic/prognostic/predictive markers in lung cancer. Exosomes can represent emerging therapeutic drug carriers. Abstract : Circulating exosomes are the major mediators of cell–cell communication. They have been found in various body fluids of healthy individuals and patients with malignancies as cargos of several molecules including miRNAs. Several studies have underlined the role of exosome miRNAs in different tumor types, including lung cancer, suggesting their potential use as biomarkers and therapeutic agents. An overview of the biology and function of exosomes and exosome miRNAs as indicators of diagnosis and treatment response in lung cancer is presented. In addition, preliminary data on exosomes as potential therapeutic agents are reported.